2023
DOI: 10.1126/sciadv.ade0718
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived semaphorin 4A improves PD-1–blocking antibody efficacy by enhancing CD8 + T cell cytotoxicity and proliferation

Abstract: Immune checkpoint inhibitors (ICIs) have caused revolutionary changes in cancer treatment, but low response rates remain a challenge. Semaphorin 4A (Sema4A) modulates the immune system through multiple mechanisms in mice, although the role of human Sema4A in the tumor microenvironment remains unclear. This study demonstrates that histologically Sema4A-positive non–small cell lung cancer (NSCLC) responded significantly better to anti–programmed cell death 1 (PD-1) antibody than Sema4A-negative NSCLC. Intriguing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…Low levels of Plexin B1 were also observed on lung Treg cells in OVA-exposed WT mice ( Figure 4C ). Plexin B1 expression was below detection by Flow cytometry on naïve CD4+ cells and low on naïve CD8+ cells in lymphoid tissues of WT mice ( Supplementary Figure S5A ) consistent with a previous study ( 39 ). However, Plexin B1 expression was highly upregulated by in vitro ConA stimulation of WT cells but not Plexin B1 KO cells ( Supplementary Figure S5B ).…”
Section: Resultssupporting
confidence: 91%
“…Low levels of Plexin B1 were also observed on lung Treg cells in OVA-exposed WT mice ( Figure 4C ). Plexin B1 expression was below detection by Flow cytometry on naïve CD4+ cells and low on naïve CD8+ cells in lymphoid tissues of WT mice ( Supplementary Figure S5A ) consistent with a previous study ( 39 ). However, Plexin B1 expression was highly upregulated by in vitro ConA stimulation of WT cells but not Plexin B1 KO cells ( Supplementary Figure S5B ).…”
Section: Resultssupporting
confidence: 91%
“…Multiplex IHC and image analysis were performed as previously reported ( 16 ). FFPE sections were incubated for 30 minutes at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…Their expression has been detected in various types of immune cells, in which their signaling has been reportedly associated with immune cell migration, differentiation, and effector functions ( 14 , 15 ). In terms of antitumor immunity, we reported that Sema4A promotes antitumor immunity through CD8 + T cell activation ( 16 ), and Sema7A interacts with integrin β1 to induce resistance to tyrosine kinase inhibitor treatment ( 17 ). Sema6D is a class VI transmembrane-type semaphorin that associates with Plexin-A1 and Plexin-A4, and functions in 2 ways: (a) stimulating receptor Plexin-As as ligands, known as forward signaling ( 18 ); and (b) interacting with Plexin-As to induce downstream Sema6D signaling, known as reverse signaling ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Semaphorin 4A (Sema4A), one of the immune semaphorins, plays both pathogenic and therapeutic roles in autoimmune diseases (Cavalcanti et al, 2020; He et al, 2023), allergic diseases (Maeda et al, 2019), and cancer (Iyer & Chapoval, 2018; Liu et al, 2018; Y. Naito et al, 2023; Pan, Wang, & Ye, 2016). While Sema4A expression on T cells is essential for T helper type 1 differentiation in the murine Propionibacterium acnes -induced inflammation model and delayed-type hypersensitivity model (Kumanogoh et al, 2005), Sema4A amplifies only T helper type 17 (Th17)-mediated inflammation in the effector phase of murine experimental autoimmune encephalomyelitis (Koda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In anti-tumor immunity, research involving human samples and murine models suggests that Sema4A expressed in cancer cells and regulatory T cells promotes tumor progression (Delgoffe et al, 2013; Liu et al, 2018; Pan et al, 2016), while other reports reveal that Sema4A in cancer cells and dendritic cells bolsters anti-tumor immunity by enhancing CD8 T cell activity (Y. Naito et al, 2023; Suga et al, 2021). In addition to these roles in immune reactions, mice with a point mutation in Sema4A develop retinal degeneration, suggesting that Sema4A is also crucial for peripheral tissue homeostasis (Nojima et al, 2013).…”
Section: Introductionmentioning
confidence: 99%